Haemodynamic effects of premedication for neonatal intubation: an observational study. Issue 2 (29th April 2019) - Truong, Linda; Kim, Jae H; Katheria, Anup C; Finer, Neil N; Marc-Aurele, Krishelle
Abstract : Objective: To examine changes in blood pressure (BP), cardiac output (CO) and cerebral regional oxygen saturation (rScO2) with administration of premedication for neonatal intubation. Design: Pilot, prospective, observational study. Oxygen saturation, heart rate, CO, rScO2 and BP data were collected. Monitoring began 5 min prior to premedication and continued until spontaneous movement. Setting: Single-centre, level 3 neonatal intensive care unit Patients: 35 infants, all gestational ages. 81 eligible infants: 66 consented, 15 refused. Interventions: Intravenous atropine, fentanyl or morphine, ±cisatracurium Main outcome measures: BP, CO, rScO2 Results: n=37 intubations. Mean gestational age and median birth weight were 31 4/7 weeks and 1511 g. After premedication, 10 episodes resulted in a BP increase from baseline and 27 in a BP decrease. Of those whose BP decreased, 17 had <20% decrease and 10 had ≥20% decrease. Those with <20% BP decrease took an average of 2.5 min to return to baseline while those with a ≥20% BP decline took an average of 15.2 min. Three did not return to baseline by 35 min. Following intubation, further declines in BP (21%–51%) were observed in eight additional cases. One infant required a bolus for persistently low BPs. CO and rScO2 changes were statistically similar between the two groups. Conclusion: About 30% of infants dropped their BP by ≥20% after premedication for elective intubation. These BP changes were not associated with any significant change in rScO2 or CO. More data are needed to better characterise the immediate haemodynamic changes and clinical outcomes associated with premedication.